A novel 3D Cu(i) coordination polymer based on Cu6Br2 and Cu2(CN)2 SBUs: in situ ligand formation and use as a naked-eye colorimetric sensor for NB and 2-NT. Issue 2 (24th November 2015) - Song, Jiang-Feng; Li, Yang; Zhou, Rui-Sha; Hu, Tuo-Ping; Wen, Yan-Liang; Shao, Jia; Cui, Xiao-Bing
Abstract : A novel 3D Cu(i ) coordination polymer based on Cu6 Br2 and Cu2 (CN)2 SBUs shows strong green light emission and sensing properties for NB and 2-NT. Abstract : A novel coordination polymer with the chemical formula [Cu4 Br(CN)(mtz)2 ] n (mtz = 5-methyl tetrazole) (1 ), has been synthesized under solvothermal conditions and characterized by elemental analysis, infrared (IR) spectroscopy, thermal gravimetric analysis, powder X-ray diffraction and single-crystal X-ray diffraction. Interestingly, the Cu(i ), CN − and mtz − in compound1 are all generated from an in situ translation of the original precursors: Cu 2+, acetonitrile and 1-methyl-5-mercapto-1, 2, 3, 4-tetrazole (Hmnt). The in situ ring-to-ring conversion of Hmnt into mtz − was found for the first time. Structural analysis reveals that compound1 is a novel 3D tetrazole-based Cu(i ) coordination polymer, containing both metal halide cluster Cu6 Br2 and metal pseudohalide cluster Cu2 (CN)2 secondary building units (SBUs), which shows an unprecedented (3, 6, 10)-connected topology. Notably, a pseudo-porphyrin structure with 16-membered rings constructed by four mtz − anions and four copper(i ) ions was observed in compound1 . The fluorescence properties of compound1 were investigated in the solid state and in various solvent emulsions, the results show that compound1 is a highly sensitive naked-eye colorimetric sensor for NB and 2-NT (NB = nitrobenzene and 2-NT = 2-nitrotoluene).